2022
DOI: 10.1021/acsinfecdis.1c00554
|View full text |Cite
|
Sign up to set email alerts
|

STING Agonist-Mediated Cytokine Secretion Is Accompanied by Monocyte Apoptosis

Abstract: The cGAS-STING (cyclic GMP-AMP synthase−stimulator of interferon genes) pathway plays a crucial role in inducing an antiviral and antitumor immune response. We studied the effects of synthetic STING agonists on several immune populations and related cytokine production. In comparison with the toll-like receptor 7 (TLR7) agonist, STING agonists induced secretion of a broader proinflammatory cytokine spectrum. Unlike the TLR7 agonist, the structurally diverse STING agonists partially depleted B and NK cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 33 publications
(118 reference statements)
6
24
0
Order By: Relevance
“…Taken together, our results observed with stimulation of purified monocytes with commonly used “normal” concentrations of STING ligands cGAMP, diABZI and MSA-2 are fully in line with previous research, i.e. our experiments confirm the reported potent stimulation of secretion of pro-inflammatory cytokines IL-1β and TNF-α associated with the simultaneous induction of massive apoptotic cell death 38 . Although Fas/CD95-dependent and spontaneous apoptosis of monocytes have been reported to induce the production of anti-inflammatory IL-10 in monocytes 39 , 40 , the STING-mediated apoptotic death did not trigger any IL-10 (and IL-19) secretion in our experiments, in line with the general assumption that the cGAS/STING pathway triggers type I IFN production via TBK1/IRF3 and pro-inflammatory cytokines via NF-κB 3 .…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, our results observed with stimulation of purified monocytes with commonly used “normal” concentrations of STING ligands cGAMP, diABZI and MSA-2 are fully in line with previous research, i.e. our experiments confirm the reported potent stimulation of secretion of pro-inflammatory cytokines IL-1β and TNF-α associated with the simultaneous induction of massive apoptotic cell death 38 . Although Fas/CD95-dependent and spontaneous apoptosis of monocytes have been reported to induce the production of anti-inflammatory IL-10 in monocytes 39 , 40 , the STING-mediated apoptotic death did not trigger any IL-10 (and IL-19) secretion in our experiments, in line with the general assumption that the cGAS/STING pathway triggers type I IFN production via TBK1/IRF3 and pro-inflammatory cytokines via NF-κB 3 .…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, the gating of functional cells could be a useful approach in therapeutic studies (cancer, autoimmune diseases, etc.). Concerning data exportation and interpretation, the frequency of cell population in live cells can be used for monitoring the changes of immune subset ratios in various pathophysiological conditions [ 40 ]. In addition, the frequency of parent population is suitable for monitoring the expression of a particular marker within the population of interest.…”
Section: Expected Results and Discussionmentioning
confidence: 99%
“…As LPS induces CD69 expression in T cells in vivo , antigen presence may be thus required . Overall, in vitro cytokine production by hNPCs in response to STING agonist treatment matched that of PBMCs . Furthermore, based on T cell activation, liver-targeted STING agonist treatment may be a viable therapeutic option.…”
mentioning
confidence: 83%
“…STING agonists potently stimulate human immune cells into producing cytokines with anticipated antiviral properties. , Yet, treating PHHs with STING agonists ( 1 – 3 ) failed to inhibit either HBV E or HBV S antigen secretion (HBe/HBsAg, Figure S1A). Nevertheless, these PHHs did not express STING under any condition analyzed in this study, as shown by immunoblotting (Figure S1B).…”
mentioning
confidence: 99%
See 1 more Smart Citation